Simulating schizophrenia through virtual reality and artificial intelligence - Cachia, Andrew; Camilleri, Vanessa; Dingli, Alexiei; Scerri, Josianne; Grech, Paulann; Sammut, Alexei (Open Science Journal, 2024)
This research project presents the use of Artificial Intelligence in a Virtual Reality simulation to immerse the player in a virtual world and experience the symptoms that a person with Schizophrenia would experience. The simulation features a number of simple tasks which the player needs to attempt, whilst at the same time facing challenges due to the effects of Schizophrenia, taking place in the form of both visual and auditory hallucinations. Artificial Intelligence is applied to the interactive narrative to allow the storyline and characters to adapt to the user’s actions, thus increasing the immersiveness of the experience. A pilot study with 58 mental health nursing students was carried out at the Department of Mental Health, University of Malta. Participant feedback from the evaluation sessions give indications that the project was well accepted and achieved the desired outcomes of increasing awareness and fostering empathy for people living with Schizophrenia. 91.4% of users who evaluated the system stated that the simulation has helped increase their understanding of Schizophrenia.